Determinants of savings frequency among tomato farmers in Ghana - Daniel Aidoo-Mensah (Cogent Economics & Finance, 2023)
AbstractMultinomial logistic regression was employed to identify the determinants underlying the respondents’ frequency of savings—weekly, monthly and seasonally. The results of the study showed that amount saved per period, number of years of education and engagement in non-farm income generating activities significantly influenced farmers’ savings frequencies. The findings are quite significant as they take the decision to save beyond the suggested two-stage sequential process to include a third stage, which is the time horizon of savings. The findings revealed that rural households are predisposed to extend their savings time horizon by holding onto their surplus funds in order to retain some capacity for their present consumption and other needs before thinking of saving. On the other hand, the anticipation of a gloomy future as a result of bad harvest for instance may induce the rural householder to shorten his/her savings time horizon, that is, reduce the time-frame s/he holds onto surplus funds and quickly save such funds. Finally, the study suggests education as a catalyst to create a desirable behaviour of saving “now” (weekly or monthly) rather than procrastinating savings to the “future” that is, saving seasonally.